Strategi Kepolisian Polrestabes Surabaya Dalam Penindakan Dan Pencegahan Tindak Pidana Judi Online Di Kota Surabaya - Dewanti, Rengganis Putri; Ismail; Kurniawan, Bagus Ananda; Rahmawati, Diana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
This study aims to analyze the strategies implemented by the Surabaya Metropolitan Police (Polrestabes Surabaya) in enforcing and preventing online gambling crimes, as well as to identify the factors that hinder the eradication process. In addition, the research discusses the measures taken by law enforcement officers to uphold the law against perpetrators of online gambling crimes in Surabaya City. According to Article 1, Paragraph (1) of Law Number 2 of 2002 concerning the Indonesian National Police, policing encompasses all matters related to the functions, institutions, and legal provisions governing police duties. Online gambling constitutes an unlawful act categorized as a criminal offense and has become increasingly prevalent in society. This research employs a qualitative approach, collecting data through interviews and documentation, with informants selected using purposive sampling, and analyzing the data descriptively in a narrative form. The findings indicate that the strategies of Polrestabes Surabaya in addressing and preventing online gambling crimes include technological innovation, effective communication, and community collaboration. The integrated implementation of pre-emptive, preventive, and repressive efforts has proven effective in uncovering numerous cases and deterring offenders. However, challenges such as low public awareness, limited cyber human resources, and the dynamics of global technology remain major obstacles that must be addressed through collaborative approaches and prevention-oriented policies for sustainable enforcement.